A study of bureaucracy in the public sector in Malaysia: a case of Tangkak District Council / Tengku Mohamad Amirulhakimi Tengku Mohd Hazrin and Muhammad Azamuddin Jamaluddin - Tengku Mohd Hazrin, Tengku Mohamad Amirulhakimi; Jamaluddin, Muhammad Azamuddin (2022)
The term "bureaucracy" also refers to a system of administration and law enforcement. a set of legal rules enacted by an organization. This paper discusses the challenges faced by employees in the Tangkak District Council when attempting to implement Weberian bureaucracy. The bureaucratic approach allows the organisation to control its services or production while also granting the manager or administrator the authority to delegate and establish administrative principles. We use data from the semi-structured interviews and observations, this research was undertaken in Tangkak District Council. It contributes to the researcher's ability to obtain information and answers to study issues. Based on the researcher's observations and the interviewees' responses, it is evident that bureaucracy features are present.